Pengaruh Manajemen Laba Terhadap Kinerja Perusahaan di Sektor Kesehatan Selama Pandemi Covid-19 - Sakti, Eklamsia; Sari Maduratna, Enggal; Firdaus, Nailufar (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The main objective of this research is to conduct empirical tests on the relationship between earnings management and company performance. The research objects are health sector companies listed on the Indonesia Stock Exchange (BEI) during 2017-2022. The research sample consisted of 72 financial report data originating from 12 companies selected based on purposive sampling. The earnings management proxy uses accrual earnings management and real earnings management. Accrual earnings management uses a modified Jones model proxy. Real earnings management uses discretionary cash flow, discretionary expenses and discretionary production costs as proxies. Company performance uses the Return on Assets (ROA) proxy. Based on the results of panel data regression using Eviews 10, accrual earnings management has a significant negative effect on financial performance. Furthermore, discretionary cash flow and discretionary expenses have a significant positive effect on company performance. Lastly, discretionary production costs have no effect on financial performance.